Underkuvade kunskaper och genealogins möjligheter (Sociologisk Forskning, 2010)
Subjugated knowledges and the possibilities of genealogyThe article explores the possibilities of “voicing” marginalized subjects by analyzing letters written by female mental patients in the beginning of the twentieth century. Following Michel Foucault, genealogy is here used as a means to explore and reclaim subjugated knowledges, i.e. knowledges that have been dismissed, distorted, disqualified and put aside by more powerful and ultimately victorious knowledge claims, in this case the psychiatric discourse. Historically oriented research on madness has often explored medical and cultural discourses and representations, as these correspond to sources that can be easily found in archives. This also means that mental patients’ own narratives and texts have been more difficult to trace, partly due to the paucity of available documentation. Herein lies a challenge: how can we represent these subjects, whose stories are inevitably always already captured and filtered by authorities, without portraying them either as passive victims or reducing them to effects of power networks? The article thus ponders research ethics, the question of Otherness and the power of representations. The difficulties in representing female patients’ “own”voices are discussed, yet the article points to the necessity of taking voices that are simultaneously in the margins and in the centre of more powerful discourses, seriously as objects of knowledge. The article argues that “the insurrection of subjugated knowledges”, i.e. bringing back such knowledges as represented here by mental patients’ narratives, opens us otherpossibilities of knowledge. Hence, mental patients’ letters are seen as important “fractures” in the official and legitimized knowledge of madness, offering alternative understandings of both committed individuals and the psychiatric discourse itself.
Keywords: mental illness; genealogy; Foucault; research ethics; letters of patients